Analisis Penjadwalan Waktu Pekerjaan Pada Proyek Jalan Kawasan Ekonomi Khusus (KEK) Pantoloan Menggunakan Linear Scheduling Method (LSM) - Asnudin, A.; Ramlan, R.; Ganiya, P.A. (Tadulako University, 2025)
A construction project is a temporary activity with a specific end goal. One of the crucial things in the construction process is work scheduling, this is because it can affect the duration and cost of the project. In the context of scheduling, methods such as Block Charts, S-Curves, Network Diagrams, and Balance Line Diagrams/Linear Scheduling Method (LSM) has been around for a long time, but in its application the scheduling method should be adjusted to the characteristics of the project to avoid losses in development. The LSM method is considered appropriate for work that is repetitive in nature. This research aims at analyzing time scheduling for road projects in the Pantoloan Special Economic Area (SEA), Central Sulawesi, using Linear Scheduling Method (LSM). The purpose of this research is to determine the comparison of scheduling and budget plans between the LSM and project methods existing. Data collection consisting of primary data and secondary data was obtained by direct observation in the field and interviews with related parties. Then a scheduling analysis is carried out with assistance software. From the research results on the scheduling of the Pantoloan KEK Road Section Handling Project in Palu City using the LSM method, the completion time was 47 days. Meanwhile, in the initial planning, a completion time of 60 days was required, so there was a difference of 13 days. The project budget plan using the LSM method obtained IDR 2.321.225.151,01. Meanwhile, the initial project budget plan is Rp. 2,365,900,000.00 so there is a cost difference of Rp. 44.674.849.- By looking at the comparison of time effectiveness, scheduling using the LSM method is more effective and efficient.